Task-Oriented Circuit Training for Mobility in Outpatient Stroke Rehabilitation in Germany and Austria: A Contextual Transferability Analysis. Issue 8 (7th April 2020) - Diermayr, Gudrun; Schomberg, Maria; Greisberger, Andrea; Elsner, Bernhard; Gronwald, Marit; Salbach, Nancy M
Abstract: People with stroke cite mobility deficits as one of the most burdensome limitations. National and international stroke guidelines recommend physical therapy based on task-oriented practice, with high numbers of repetitions to improve mobility. In the outpatient setting in Germany and Austria, these principles have not yet been established. The purpose of this study was to identify an evidence-based intervention that could help reduce this research-practice gap. A stepwise approach proposed by Voigt-Radloff and colleagues and Cochrane Germany was used. First, the specific health service problem in the German and Austrian physical therapy outpatient context was identified. Second, a promising intervention was identified using a systematic search in the Cochrane Library and by grading the quality of the evidence using the Grading of Recommendations Assessment, Development and Evaluation. Finally, the transferability of the promising intervention into the local context was evaluated using predefined questions from the Cochrane guide and reports from health insurances, professional organizations, and national stroke guidelines. Task-oriented circuit training reviewed by English and colleagues was chosen. The review showed clinically important improvements in walking distance and speed. The quality of the evidence was graded high for these 2 outcomes. We identified contextual challenges for implementation at the setting level (eg, insufficient reimbursement for group therapy by insurance companies), the participant and therapist level (eg, unknown motivation for group therapy due to the established 1:1 patient-therapist ratio), and the outcome measure level (eg, lack of standardized, cross-culturally translated manuals). Although task-oriented circuit training is scientifically well established, barriers to implementation into routine care in Germany and Austria can be expected. In a next step, research using knowledge translation methodology will focus on the detailed evaluation of barriers and facilitators with relevant stakeholders.